Late blood pressure reduction in SHR subjected to transient captopril treatment in youth: possible mechanisms - Zicha, J; Dobešová, Z; Kunes, J (Physiological research, 2008)
Spontaneously hypertensive rats (SHR) are characterized by enhanced nifedipine-sensitive component of sympathetic vasoconstriction. Our study tried to elucidate the mechanisms responsible for long-term reduction of blood pressure (BP) in SHR subjected to early transient captopril treatment. Adult untreated SHR aged 30-34 weeks were compared with animals subjected to chronic captopril treatment for 6 weeks either in youth (between 4 and 10 weeks of age) or in adulthood (between 24 and 30 weeks of age). Antihypertensive effects of captopril were more pronounced in young than adult SHR. This was due to greater attenuation of sympathetic and nifedipine-sensitive BP components and prevention of residual BP rise in young captopril-treated SHR in which the reductions of nifedipine-sensitive BP component and residual BP persisted for 20 weeks after captopril withdrawal. The magnitude of nifedipine-sensitive component of sympathetic vasoconstriction is decisive for BP maintenance not only in untreated SHR but also in SHR during active captopril treatment by or after its withdrawal.
Keywords: krevní tlak; sympatický nervový systém; hypertenze; Nifedipine; vazodilatancia; Vasodilator Agents; Rats, Inbred SHR; Blood Pressure; potkani inbrední SHR; inhibitory ACE; krysa rodu Rattus; rozvrh dávkování léků; Sympathetic Nervous System; věkové faktory; Antihypertensive Agents; vazokonstrikce; antihypertenziva; Disease Models, Animal; mužské pohlaví; Vasoconstriction; Hypertension; zvířata; Drug Administration Schedule; Age Factors; Rats; Animals; kaptopril; Male; Angiotensin-Converting Enzyme Inhibitors; modely nemocí na zvířatech; nifedipin; Captopril